The practice of industrial policy government-business coordination in Africa and East Asia - edited by John Page (Oxford Oxford University Press, 2017)
Much of the information relevant to policy formulation for industrial development is held by the private sector, not by public officials. There is therefore fairly broad agreement in the development literature that some form of structured engagement, often referred to as close or strategic coordination, between the public and private sectors is needed, both to assist in the design of appropriate policies and to provide feedback on their implementation. There is less agreement on how that engagement should be structured, how its objectives should be defined, and how success should be measured. In fact, the academic literature on close coordination provides little practical guidance on how governments interested in developing a framework for government business engagement should go about doing it.
Includes bibliographical references and index.
Keywords: Industrial policy--East Asia